2007
DOI: 10.1002/ajpa.20579
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of Ribeirinhos in Brazil and the nutrition transition

Abstract: Anthropometric and household data (size, composition, economic activity) were collected from a population of Ribeirinhos living in a rural setting in the eastern Amazon. Data are compared to international reference standards and to other Amazonian populations with the goals of increasing our understanding of the Amazon's largest ethnic group and identifying the relationship between changes in subsistence strategies and nutritional status. Data on height, weight, skinfolds, and circumferences were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
0
16

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 35 publications
8
60
0
16
Order By: Relevance
“…Why is this? Bitter manioc, which is processed into farinha, is both the fundamental carbohydrate energy source and often the most important market crop for caboclo populations throughout Brazilian Amazonia (Murrieta and Dufour, 2004;Piperata and Dufour, 2007;Piperata, 2007). The municipality of Manicoré is said to be the biggest producer of farinha in the whole of Amazonas state 6 .…”
Section: Manioc and Dark Earths Todaymentioning
confidence: 99%
“…Why is this? Bitter manioc, which is processed into farinha, is both the fundamental carbohydrate energy source and often the most important market crop for caboclo populations throughout Brazilian Amazonia (Murrieta and Dufour, 2004;Piperata and Dufour, 2007;Piperata, 2007). The municipality of Manicoré is said to be the biggest producer of farinha in the whole of Amazonas state 6 .…”
Section: Manioc and Dark Earths Todaymentioning
confidence: 99%
“…Although fishing activities may accidentally catch turtles, which in turn could be consumed by our interviewees, this was not a common phenomena. This suggests that current patterns of Amazonian development and associated nutritional changes (PIPERATA 2007, PIPERATA et al 2011) may reduce demand for adult turtles. Therefore direct anthropogenic impacts on freshwater turtle populations (e.g.…”
Section: Turtle Egg Consumptionmentioning
confidence: 99%
“…There are two non-mutually exclusive explanations for these differences: differences in P. unifilis abundances and differences in harvest levels for personal and commercial use. The depletion of P. unifilis abundances around more developed areas is well documented and human egg consumption is therefore likely to decrease as a result of decreased abundances close to human settlements especially when alternative food sources are available (PIPERATA 2007, PIPERATA et al 2011. REBÊLO et al (2005) found a 10 fold reduction in P. unifilis egg harvests close to human settlements, which was also related to a clear separation between the number of eggs collected for personal consumption and commercial trade.…”
Section: Turtle Egg Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueles que foram realizados na Amazônia demonstram uma tendência de mudança da alimentação nas formas de uso dos recursos naturais (PIPERATA, 2007;NARDOTO et al 2011;PIPERATA et al 2011). Neste contexto de mudança, quais seriam os impactos da modernidade, do desenvolvimento econômico, da urbanização, das politicas públicas de transferência de renda, do maior acesso a itens industrializados de supermercado no modo de vida de povos tradicionais?…”
Section: Introductionunclassified